Weakly G-Supplemented Modules (European Journal of Pure and Applied Mathematics, 2017)
In this work, we define weakly g-supplemented modules and cofinitely weak g-supplemented modules. We investigate some properties of these modules. We show that the finite sum of weakly g-supplemented modules is weakly g-supplemented, an arbitrary sum of cofinitely weak gsupplemented modules is cofinitely weak g-supplemented. We also define g-semilocal modules and give some equivalencies for weakly g-supplemented, cofinitely weak g-supplemented and g-semilocal modules.